How to build your own digital signature in your Web site - Al Nawaj'ha, Fawwaz Yousef; Abutaha, Mohammed (IEEE, 2013)
This paper aimed to clarify the concept of the digital signature, and its usage in Web site security

specially in integrity, non-repudiation, and in authentication. The paper also illustrates how to choose one or more digital signature algorithms (Hybrid algorithm) and apply it practically in your Web site.